An Analysis of Building Students’ Character in Romania and Indonesia - Marmoah, Sri; Diana Sinziana Duca, Aurora Adina Colomeischi, (Opción, 2019)
Educational systems are implemented in both Romania and Indonesia to build students' character for quality education. Based on descriptive analysis, the aim of this paper is to report some findings of how students’ character is built in Romania and Indonesia. As a result, Indonesia and Romania share similar aspects in building students’ characters, and what inhibits the latter is summed up by the lack of parent participation, difficulties at social and institutional levels, and individual differences. In conclusion, there are three critical points in the differences between character building: integration in the subject, integration in local content, and self-development activities.